Pengaruh Metode Demonstrasi Melalui Film Animasi Pada Kecakapan Menulis Narasi Siswa Sekolah Dasar - Dinda Vica Deminda; Mubarak Ahmad (UNDIKMA, 2022)
This study aimed to determine the impact of the demonstration method that was conducted through animation movie on the narration writing skills of elementary school students. This study was conducted using a quantitative research approach, with Quasi-Experimental Design (Posttest Only Control Design) as a research method. Participants were divided into two groups, namely the experimental class and the control class, with each group consisted of 33 students. The results of a study showed that the posttest mean value of the experimental class was higher, which was 76.30, compared to the score in the control class, which was 63.51. This study establishes that the use of an animation movie as a teaching tool for students at Elementary School 12 in Depok had an impact on students' narration writing skills. Through the use of animation movie, students become more enthusiastic and active when participating in learning activity.